Percepción sobre la biodiversidad en fincas agropecuarias en la zona sur de Cartago, Costa Rica - González-Jiménez, Ximena Leonor (2025)
Understanding how farmers perceive biodiversity is essential for promoting agricultural practices that respect local ecosystems. Furthermore, understanding their realities and needs allows for effective and sustainable conservation efforts, strengthening the relationship between agriculture and biodiversity. This study analyzes how farmers in southern Cartago perceive changes in the natural environment and how these influence their agricultural activities. To this end, interviews were conducted with farm owners in Cachí, Orosi, Ujarrás, and Paraíso. Of those interviewed, 83.3% agreed that wild animals provide benefits to agricultural activities through their role in pest control, pollination, and seed dispersal. Meanwhile, 93.3% stated that flora is also beneficial due to the production of shade, oxygen, and fruit. In contrast, 66.7% of people acknowledged the presence of harmful animals, and 53.3% noted that certain plants or trees negatively affect their agricultural activities. These results reflect a certain awareness of the role of biodiversity in agriculture, as well as recognition of the negative effects that practices such as deforestation and the use of agrochemicals have on ecosystems.